ASSESSMENT OF SEAWATER INTRUSION IN FUSHE KUQE AQUIFER, ALBANIA - Cenameri, S.; Beqiraj, A. (Bulletin of the Geological Society of Greece, 2016)
The Fushë Kuqe costal aquifer is a typical confined alluvial aquifer. The aquifer medium consists of alternating and discontinuous layers of gravel and sand-gravel with and silt-clay impermeable layers which have conditioned its multilayer character. The aquifer recharge occurs mainly through water infiltration from the Mat river in the North, and from Droja river in the South, while its natural discharge proceeds to the Adriatic sea. As from the variation of chloride and TDS content in groundwater, an advancement of sea water intrusion into aquifer fresh water was evidenced. The direction of sea water wedge from coastal southwestern sectors towards the Gorre and Fushe Kuqe where pumping station are located, favors the opinion that it was caused by a decrease of groundwater pressure due to the groundwater pumping. The increase of chloride content in groundwater through time confirms that sea water intrusion towards the fresh aquifer water is still ad-vancing and is caused by both intensification of groundwater pumping for public water supply and by the drilling of artesian private wells.